Pengaruh Panjang Hari, Asam Indol Asetat, dan Fosfor terhadap Tanaman Kedelai dan Kualitas Benih dalam Penyimpanan - Rudi Hartawan; Zainal Ridho Djafar; Zaidan Panji Negara; Mery Hasmeda; , Zulkarnain (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2011)
The objective of this study was to investigate the effect of photoperiod, indole acetic acid (IAA), and phosphorus on soybean plant growth and seed quality during storage. The trial was carried out at Sebapo Experimental Station, Jambi, Center for Post Harvest Research and Development, The Ministry of Agriculture and Center for Forest Research and Development, The Ministry of Forestry, Bogor from November 2009 until June 2010. Split-split plot design was used consisted of three factors, i.e. photoperiods (12 and 14 hours 54 minutes) as the main plot, concentrations of IAA (0, 75, and 150 ppm) as subplot, and dosages of phosphorus (0, 60, and 120 kg P2O5 ha-1) as subplot. The result showed that photoperiod, IAA, and phosphorus application had significantly improved production and seed quality. The path analysis showed that the weight of 1,000 seeds affected other variables. The seed protein content has the largest path coefficient compared to other variables. The treatment of mother plant with 14 hours 54 minutes photoperiod combined with IAA of 150 ppm and P2O5 of 120 kg ha-1 resulted in the highest seed quality during 90 days of storage in room temperature.